Ultrasound detection of prostatic calculi as a parameter to predict the appearance of hematospermia after a prostate biopsy - Lucio Dell'Atti (International Brazilian Journal of Urology)
ABSTRACT Purpose: We evaluated the correlation between prostate calculi and hematospermia in patients undergoing prostate biopsy, and its impact on sexual activity of patients. Materials and Methods: A single-center prospective randomized study of 212 patients referred for transrectal ultrasound-guided prostate biopsy (TRUSBx) was performed. All patients were divided into two groups: Group A (GA), 106 patients with moderate/marked presence of prostatic calculi visualized by TRUS; Group B (GB), 106 patients with absence/scarce of prostatic calcifications. Patients were handed questionnaires to obtain a validated data on the duration and impact of hematospermia on sexual activity. The anxiety scores were recorded using a visual analogue scale. Results: No significant difference was noted between the two groups when comparing age, preoperative PSA level, prostate volume, and biopsy number, except for digital rectal examination (DRE) findings. Post-biopsy results of patients included in GA revealed that the complication of hematospermia was present in 65.1%, while in GB was present in 39.7% (p<0.001). On multivariate analysis for identifying significant preoperative predictors of hematospermia, which included variables of age, PSA, prostate volume, and prostate cancer were not shown to be significant predictors of hematospermia, except DRE and prostate calculi (p<0.001). The mean anxiety score was 3.7±2.8 in GA and 2.3±1.9 in GB, respectively (p<0.001). Conclusions: Prostatic calculi are an independent predictive factor of severe hematospermia after TRUSBx on the basis of multivariate analysis, but don't affect the positive rate of prostate cancer. Patients should be adequately counselled before TRUSBx to avoid undue anxiety and alterations in sexual activity.